ELEKTR ZARYADLARNING SHARLARDA O’ZARO TAQSIMLANISHIGA OID BIR MASALA XUSUSIDA - Yavidov, B.; Ollomberganova, M.Sultonova, M.; Nurimbetov, K.; Narbayeva, S. (SCIENCE and SOCIETY, 2020)
In the article the issues on distribution of electric charges between solid spheres are considered. The problem is solved by standard and nonstandard methods. It is stated that in formulation of the problem on distribution of electrical charges between solid spheres a correspondence between a total number of particles in solid spheres and ratio of linear sizes of solid spheres should be taken into account.
Keywords: electric charge; charged balls; potential; charge distribution; methodology for solving problems